Bioenergetic Failure Drives Functional Exhaustion of Monocytes in Acute-on-Chronic Liver Failure - Deepanshu Maheshwari; Dhananjay Kumar; Rakesh Kumar Jagdish; Nidhi Nautiyal; Ashinikumar Hidam; Rekha Kumari; Rashi Sehgal; Nirupama Trehanpati; Sukriti Baweja; Guresh Kumar; Swati Sinha; Meenu Bajpai; et al. (Frontiers in Immunology, 2022)
ObjectiveThe monocyte–macrophage system is central to the host’s innate immune defense and in resolving injury. It is reported to be dysfunctional in acute-on-chronic liver failure (ACLF). The disease-associated alterations in ACLF monocytes are not fully understood. We investigated the mechanism of monocytes’ functional exhaustion and the role of umbilical cord mesenchymal stem cells (ucMSCs) in re-energizing monocytes in ACLF.DesignMonocytes were isolated from the peripheral blood of ACLF patients (n = 34) and matched healthy controls (n = 7) and patients with compensated cirrhosis (n = 7); phagocytic function, oxidative burst, and bioenergetics were analyzed. In the ACLF mouse model, ucMSCs were infused intravenously, and animals were sacrificed at 24 h and day 11 to assess changes in monocyte function, liver injury, and regeneration.ResultsPatients with ACLF (alcohol 64%) compared with healthy controls and those with compensated cirrhosis had an increased number of peripheral blood monocytes (p < 0.0001) which displayed significant defects in phagocytic (p < 0.0001) and oxidative burst capacity (p < 0.0001). ACLF patients also showed a significant increase in the number of liver macrophages as compared with healthy controls (p < 0.001). Bioenergetic analysis showed markedly reduced oxidative phosphorylation (p < 0.0001) and glycolysis (p < 0.001) in ACLF monocytes. Patients with monocytes having maximum mitochondrial respiration of <37.9 pmol/min [AUC = 0.822, hazard ratio (HR) = 4.5] and baseline glycolysis of ≤42.7 mpH/min (AUC = 0.901, HR = 9.1) showed increased 28-day mortality (p < 0.001). Co-culturing ACLF monocytes with ucMSC showed improved mitochondrial respiration (p < 0.01) and phagocytosis (p < 0.0001). Furthermore, ucMSC therapy increased monocyte energy (p < 0.01) and phagocytosis (p < 0.001), reduced hepatic injury, and enhanced hepatocyte regeneration in ACLF animals.ConclusionBioenergetic failure drives the functional exhaustion of monocytes in ACLF. ucMSCs resuscitate monocyte energy and prevent its exhaustion. Restoring monocyte function can ameliorate hepatic injury and promote liver regeneration in the animal model of ACLF.